2014
DOI: 10.1089/big.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

From Pharmacovigilance to Clinical Care Optimization

Abstract: In order to ensure the continued, safe administration of pharmaceuticals, particularly those agents that have been recently introduced into the market, there is a need for improved surveillance after product release. This is particularly so because drugs are used by a variety of patients whose particular characteristics may not have been fully captured in the original market approval studies. Even well-conducted, randomized controlled trials are likely to have excluded a large proportion of individuals because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…These methods have been deployed in the research context in screening and diagnosis and prediction of future events ( Table 1 ). These deployments are in disparate areas, typically in hospital rather than community setting, and in the vast majority of cases based on data from single centers, with implications for reproducibility [ 11 ] and generalizability [ 12 ]. However, the rapid pace of development of machine learning continues both within health care and more broadly across all information processing tasks in society [ 13 ].…”
Section: Ai and Decision Making In Health Systemsmentioning
confidence: 99%
“…These methods have been deployed in the research context in screening and diagnosis and prediction of future events ( Table 1 ). These deployments are in disparate areas, typically in hospital rather than community setting, and in the vast majority of cases based on data from single centers, with implications for reproducibility [ 11 ] and generalizability [ 12 ]. However, the rapid pace of development of machine learning continues both within health care and more broadly across all information processing tasks in society [ 13 ].…”
Section: Ai and Decision Making In Health Systemsmentioning
confidence: 99%
“…The essential starting point of the individual patient can be enhanced by the knowledge present in population-level databases, and the resulting information combinations and comparisons used to make informed clinical decisions. In turn, the information accumulated from individuals benefits the healthcare of the entire population.
Figure 4 Clinical care optimization: a Big Data model for efficient targeting of tests and treatments and vigilance for adverse events (figure courtesy of Kai-ou Tang and Edward Moseley, from [21] with permission).
…”
Section: Establishing Knowledgementioning
confidence: 99%
“…Pharmaceuticals are often prescribed to a large, diverse patient population that may have not been adequately represented in pre-release clinical trials. In fact, RCT cohorts may deliberately be relatively homogeneous in order to capture the intended effect(s) of a medication without "noise" from co-morbidities that could modulate treatment effects [28]. Humphreys and colleagues (2013) reported that in highly-cited clinical trials, 40 % of identified patients with the condition under consideration were not enrolled, mainly due to restrictive eligibility criteria [29].…”
Section: Demonstrating the Power Of Secondary Ehr Analysis: Examples mentioning
confidence: 99%
“…Humphreys and colleagues (2013) reported that in highly-cited clinical trials, 40 % of identified patients with the condition under consideration were not enrolled, mainly due to restrictive eligibility criteria [29]. Variation in trial design (comparators, endpoints, duration of follow-up) as well as trial size limit their ability to detect low-frequency or long-term side-effects and adverse events [28]. Post-market surveillance reports are imperfectly collected, are not regularly amalgamated, and may not be publically accessible to support clinical-decision making by physicians or inform decisionmaking by patients.…”
Section: Demonstrating the Power Of Secondary Ehr Analysis: Examples mentioning
confidence: 99%